Manual of neonatal care - Cloherty, John P. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
"This edition of the Manual of Neonatal Care has been completely updated and extensively revised to reflect the changes in fetal, perinatal, and neonatal care that have occurred since the sixth edition. In addition, we welcome Anne Hansen from Harvard as a new editor and collaborator. In the Manual, we describe our current and practical approaches to evaluation and management of conditions encountered in the fetus and the newborn, as practiced in high volume clinical services that include contemporary prenatal and postnatal care of infants with routine as well as complex medical and surgical problems. Although we base our practice on the best available evidence, we recognize that many areas of controversy exist, that there is often more than one approach to a problem, and that our knowledge continues to grow. Our commitment to values, including clinical excellence, multidisciplinary collaboration, teamwork, and family-centered care, is evident throughout the book. Support of families is reflected in our chapters on Breastfeeding, Developmental Care, Bereavement, and Decision Making and Ethical Dilemmas. The Children's Hospital Boston Neonatology Program at Harvard has grown to include 57 attending neonatologists and 18 fellows who care for more than 28,000 newborns delivered annually at the Beth Israel Deaconess Medical Center (BIDMC), the Brigham and Women's Hospital (BWH) (formerly the Boston Lying-In Hospital and the Boston Hospital for Women), Beverly Hospital, Saint Elizabeth's Medical Center, Holy Family Hospital, Good Samaritan Medical Center, South Shore Hospital, and Winchester Hospital"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Neonatology -- Handbooks, manuals, etc; Electronic books